Works and celebrations in the integration of the Chinese in Chiapas. From historical proceeding to current ethnic definition (Tzintzun, Revista de Estudios Históricos, 2016)
The long history of Chinese immigrants in Mexico has been observed,from historiography, linked to the national state building in the postrevolutionperiod. The campaigns against their presence on Mexican soil,and their xenophobic character contrast with other processes in someparts of the Republic as in the case of Chiapas, where the Chinese weregradually incorporated to the host society. Some organizations helpedin this integration. However, the current debates on the nature of theChinese ethnic group in Mexico distort, rather than help, to understandwhat happened. For this reason, the article seeks to present evidenceabout that historical process. At the same time it discusses the ethnicdefinitions people apply in the present.
Keywords: Chiapas; Chinese; culture; ethnicity; integration